돌봄당사자의 상호관계 유형: 공식/비공식 노인돌봄을 중심으로 - 주현정; Joo Hyun-jung; 남일성; Nam Il-sung (공공정책연구, 2021)
본 연구의 목적은 노인돌봄의 주요 주체로서 공식과 비공식 돌봄 당사자들의 상호협력은 어떠한 모습으로 나타나고 있는지 각 입장의 경험을 드러냄으로써 다양한 관계 유형을 탐색해보는 데 있다. 이를 위해 데이케어센터의 돌봄 제공자 10명, 보호자 2명, 이용자 1명을 대상으로 심층 인터뷰를 진행한 후 본질적 사례연구 방법을 적용하여 이들의 인식과 현실적 맥락을 이해하고자 하였다. 분석 결과, 기관 종사자와 보호자 간 관계 유형은 각 입장에서의 상호 인식을 교차할 때 9가지 매트릭스로 도출 가능하였다. 이들 유형에서 ‘책임전가형’, ‘보호자 아집형’, ‘제공자 위축형’, ‘보호자 응대형’, ‘보호자 주도형’ 등은 부정적인 관계 유형으로, ‘역할분담형’, ‘소비자 참여형’, ‘상호존중형’, ‘상호의존형’ 등은 긍정적인 관계 유형으로 파악할 수 있었다. 이러한 결과를 바탕으로 공식과 비공식 돌봄 당사자들의 상호협력이 긍정적 또는 부정적 형태를 보이는 요인을 논하면서 노인돌봄의 본질적인 가치라 할 수 있는 좋은 돌봄을 위해서 필요한 방향을 제안하였다. The purpose of study is to explore various relationship types of mutual cooperation between formal and informal direct carers of the elderly by the experiences of each party. To fulfill the study purpose, in-depth interviews of care providers 10, family members 2 and a service user were conducted, and essential case study was applied to understand their perception of each others and practical contexts. The study result enabled to draw 9 metrics of relationship types when the mutual perceptions of each direct care parties were intercrossed. Negative relationship type includes ‘responsibility imputation type’, ‘obstinate family member type’, ‘discouraged provider type’, ‘response obsessing family member type’ and ‘family member leading type’. positive relationship type includes ‘responsibility sharing type’, ‘user invole type’, ‘mutual respecting type’ and ‘interdepending type’. Based on the analysis, influencing factors on forming positive or negative types were discussed and neccessary measures to be taken for good care, essencial value of elderly care were suggested.